2019
DOI: 10.4274/tjps.galenos.2018.99267
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Quantification, and Antioxidant Activity of Hydroalcoholic Extract of <i>Artemisia campestris</i> from Algeria

Abstract: Amaç: Bu çalışmada, Cezayir'de yetişen Artemisia campestris'in sulu alkollü ekstresinin kimyasal profilinin ve antioksidan etkisinin araştırılması amaçlanmıştır. Gereç ve Yöntemler: Cezayir'de yetişen A. campestris'in sulu alkollü ekstresinin fenolik bileşenleri yüksek performanslı sıvı kromatografisi (HPLC) diyot dizinli dedektör-(DAD)-elektrosprey iyonizasyonu (ESI)-mass spektrometresi (MS)/MS kullanılarak incelenmiştir. İn vitro antioksidan aktivite ve toplam fenolik içerik de sırasıyla oksijen radikal abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Overproduction of reactive species such as reactive oxygen species (ROS) and reactive nitrogen species (RNS) leads to generation of a phenomenon known as oxidative stress. Oxidative stress represents the imbalance between the production rate of free radicals and the antioxidants in the human body, which may be followed by several health disorders, including cancer, cardiovascular diseases, inflammation, and Alzheimer’s disease [ 32 , 33 ]. Previous studies revealed a positive linear correlation between the antioxidant activities of the tested endophytic fungal extracts and the presence of certain chemical classes in these extracts, including phenolic acid and quinone derivatives [ 34 ], indole derivatives [ 6 ], coumarins [ 35 ], and butyrolactones [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overproduction of reactive species such as reactive oxygen species (ROS) and reactive nitrogen species (RNS) leads to generation of a phenomenon known as oxidative stress. Oxidative stress represents the imbalance between the production rate of free radicals and the antioxidants in the human body, which may be followed by several health disorders, including cancer, cardiovascular diseases, inflammation, and Alzheimer’s disease [ 32 , 33 ]. Previous studies revealed a positive linear correlation between the antioxidant activities of the tested endophytic fungal extracts and the presence of certain chemical classes in these extracts, including phenolic acid and quinone derivatives [ 34 ], indole derivatives [ 6 ], coumarins [ 35 ], and butyrolactones [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the most useful EO applications, their use as antioxidant agents is highly investigated, since the phenomenon known as oxidative stress is the root of several health problems, like inflammations, cancer, neurodegeneration and cardiovascular diseases. The over-production of free radicals, highly energetic molecules containing odd electrons, mostly represented by reactive oxygen species (ROS), is involved in this phenomenon; as naturally occurring antioxidant agents, EOs may attenuate this damage through their radical scavenging effect [7][8][9][10][11]. Among the neurodegenerative diseases sustained by inflammation, Alzheimer s disease (AD) represents the predominant reason of dementia in old people.…”
Section: Introductionmentioning
confidence: 99%
“…The essential oil of A. campestris has been isolated and investigated for its chemical composition and biological activities by several authors in Algeria (Belhattab et al 2011;Ghorab et al 2013;Boutemak et al 2017;Medila et al 2017;Bakchiche et al 2019) and other countries (Neffati et al 2008;Costa et al 2009;Judzentienea et al 2010;Akrout et al 2003Akrout et al , 2010Dib et al 2017). Only two investigations has been provided on the essential oil of P. arabica concerning the analysis of its chemical constituents (Mossa et al 1987;Djermane et al 2016).…”
Section: Introductionmentioning
confidence: 99%